2020
DOI: 10.1029/2019ja027277
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the Role of Alfvén Waves in Global Field‐Aligned Current System Dynamics During Southward IMF: Swarm Observations

Abstract: Field-aligned currents (FACs) are a primary signature of magnetosphere-ionosphere coupling (MIC). However, establishing FACs requires the propagation of Alfvén waves. Large-scale quasi-static FACs are well-organized into large-scale Region 1 (R1) and Region 2 (R2) systems during intervals of southward interplanetary magnetic field (IMF); however, the scale-dependent spatiotemporal variability and related electrodynamics are less well understood. Using the electric and magnetic field data from Swarms A and C, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
(152 reference statements)
0
15
1
Order By: Relevance
“…Stronger NH FACS, as reported here, would also support stronger NH closing currents. Pakhotin et al (2019Pakhotin et al ( , 2020 argued that dB and FACs with scales < ~ 150 km are more appropriately treated as incident, ionospherically reflected, and interfering Alfvén waves. In their view, an Alfvén wave paradigm could/should be used to accurately describe the entire spectrum of scale sizes involved in MI coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger NH FACS, as reported here, would also support stronger NH closing currents. Pakhotin et al (2019Pakhotin et al ( , 2020 argued that dB and FACs with scales < ~ 150 km are more appropriately treated as incident, ionospherically reflected, and interfering Alfvén waves. In their view, an Alfvén wave paradigm could/should be used to accurately describe the entire spectrum of scale sizes involved in MI coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that to some degree, similar behaviour can be inferred in terms of FACs 12 which must logically be associated with these electromagnetic perturbations as well—especially since they are related to Alfvén wave dynamics. For example, previous observational studies have made the link between Alfvénic disturbances and FACs, and have suggested that both may be explained as part of the same physical framework which can explain the characteristics of MIC at these scales 17 , 24 , 27 , 28 . This study is the first to demonstrate that, when seasonally averaged, the high-latitude electromagnetic Poynting flux observed across a wide range of scales has a definitive northern preference both on the dayside and on the nightside.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile on the dayside, the southern oval also similarly experiences more variation in solar illumination than the north, potentially traversing further into and dwelling longer in sunlit dayside regions where there is expected to be a greater mismatch between the Pedersen and Alfvén impedances as a result of increased background Pedersen conductance due to dayside solar EUV illumination. This would be expected to lead to greater median Alfvén wave ionospheric reflection coefficients in the south, as per the ionospherically reflecting Alfvén wave paradigm 16,17,23,24 . In turn this could lead to a stronger reflection of Poynting flux from the southern ionosphere back towards the equator than in the north.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that to some degree, similar behaviour can be inferred in terms of FACs 12 which must logically be associated with these electromagnetic perturbations as well-especially since they are related to Alfvén wave dynamics. For example, previous observational studies have made the link between Alfvénic disturbances and FACs, and have suggested that both may be explained as part of the same physical framework which can explain the characteristics of MIC at these scales 17,24,27,28 . This study is the first to demonstrate that, when seasonally averaged, the high-latitude electromagnetic Poynting flux observed across a wide range of scales has a definitive northern preference both on the dayside and on the nightside.…”
Section: Discussionmentioning
confidence: 99%